THE INFLUENCE OF WORK ENVIRONMENT AND OCCUPATIONAL SAFETY AND HEALTH ON THE PERFORMANCE OF EMPLOYEES OF THE YOROZU AUTOMOTIVE INDONESIA COMPANY - Lilis Nurkholisoh; Aji Tuhagana; Zenita Apriania (PT. Berkah Digital Teknologi, 2024)
Purpose: This research was conducted with the aim of knowing and analyzing the work environment and occupational safety and health (K3) on employee performance at PT Yorozu Automotive Indonesia. Research Methodology: This research uses survey research methods. The population in this study were employees of PT Yorozu Automotive Indonesia. The total population is 176 people, and a sample of 64 employees was taken from the population with a data collection technique using simple random cluster sampling. This research uses data collection methods in the form of interviews, questionnaires and documentation studies. The data analysis method used is multiple linear regression analysis. Results: The results of the analysis state that occupational safety and health (K3) is classified as good, the work environment is classified as very good, and employee performance is classified as good. Based on this research, there is an influence of occupational safety and health (K3) and the work environment on employee performance at PT Yorozu Automotive Indonesia where the increasing work environment and K3 means that employee performance will also increase. The results show that the most dominant variable in employee performance is occupational safety and health (K3). Limitations: The study only focuses on the influence of work environment and occupational safety and health (K3) on employee performance at PT Yorozu Automotive Indonesia. Contribution: The findings of this study provide insights for management on the importance of maintaining a good work environment and implementing effective occupational safety and health (K3) programs to improve employee performance.